(untitled) (Texas Journal of Philology, Culture and History, 2025)
This article examines the characteristics, origins, and sociolinguistic functions of youth slang in Uzbek and English, providing a comparative analysis of lexical, morphological, and semantic aspects. The study explores the influence of globalization, digital communication, and cross-cultural interaction on the emergence and spread of slang expressions among young speakers. Attention is given to the borrowing and adaptation of foreign lexical units, hybrid word formation, and the role of mass media and social networks in disseminating youth slang. The research identifies common trends in slang usage across both languages, as well as culturally specific features that reflect the unique sociolinguistic environment of each language community.